The Performance Measurement Frameworks in Healthcare: Scopus Study. (June 2021) - Zaadoud, B.; Chbab, Y.; Chaouch, A.
Object: The purpose of this article is to analyse and compare the frameworks of performance measurement in primary health care in the world. The objective is to determine whether the frameworks of performance measurement in primary health care have an influence on the performance of health centres. Method: We conducted a systematic review of the literature to: (a) identify a conceptual framework for measuring quality management systems; and (b) assess the effects of the conceptual framework on quality improvement and quality of care outcomes. We chose frameworks highly cited in the literature and analysed and compared these frameworks. Results: Eight dimensions were identified for assessing performance in primary health care facilities (PHCFs) in more than 50% frameworks: effectiveness, safety, accessibility, equity, efficiency, acceptability, patient-centredness and timeliness. Conclusion: Even if the links are not established within the framework of a scientific research, quality approaches are generally recognised as an essential tool to help establishments improve their quality of care and the safety of their patients. Until now, the evaluation of the quality of care in the 'PHCF' is not yet in place, a blatant need for performance measurement tools, relevant information, coherence between the operational and strategic levels, integration of organizational objectives in the measurement of performance in order to direct the structures towards a true management by quality.